Effect of Ozone in Freund’s Complete Adjuvant-Induced Arthritis - Gülnur TAŞÇI BOZBAŞ; Mustafa YILMAZ; Esra PAŞAOĞLU; Gülcan GÜRER; Rasime İVGİN and Buket DEMİRCİ (Archives of Rheumatology, 2018)
Objectives: This study aims to investigate the effectiveness and reliability of ozone (O3) in Freund’s complete adjuvant (FCA)-induced arthritis, an animal model for rheumatoid arthritis. Materials and methods: Thirty-six four- to five-month-old male Wistar rats weighing between 274-420 gr were used in this study. Saline was injected into the hind paws of half of these rats, and FCA was injected into the other half. At the end of two weeks, 40 μg of O3 was administered to nine rats from each group twice a week for seven total doses. The rats were followed-up in terms of clinical findings. At the sixth week, the rats were sacrificed and serum malondialdehyde, glutathione peroxidase, and superoxide dismutase levels were measured. In addition, ankle joints were separated for histopathological examination. Results: Significant improvement was observed in terms of hind-paw diameter, severity of arthritis, and histopathological findings of inflammation after O3 treatment in the group with FCA-induced arthritis. Although it was not quite significant, an upward trend was detected in oxidative stress markers with O3 treatment. Conclusion: This study, the first to investigate the effects of systemic O3 on the clinical and histopathological outcomes of rheumatoid arthritis, indicates that O3 is a highly effective and reliable treatment method in FCA-induced arthritis in animal models.